(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Arterial hypertension (high blood pressure) is one of the most common chronic diseases and, if uncontrolled, can lead to very serious complications. The risk of heart attack, stroke, heart failure, hypertensive retinopathy, and hypertensive nephropathy increases as a result of this condition [1-3,10]. Hypertension is often called a "silent killer" because clinical symptoms are frequently mild or even absent. This makes the condition particularly dangerous, as it can progress unnoticed and only be detected after complications arise [4,5,11,12].